APPLICATION OF EDUCATIONAL INNOVATION AND SOCIAL CHANGE TO LEARNING COMPONENTS - Oktariani; Suyuti (International Journal of Teaching and Learning, 2024)
Educational innovation covers issues related to the components of the education system, both in the narrow sense, namely the level of educational institutions, and in the broad sense, namely the national education system. Education has great social importance, especially in modern complex industrial societies. This is one of the concrete sources of information and knowledge that influences society. The role of education as a means of social change and social development or as an agent is widely accepted in today's society. Education is responsible for the preservation, communication and dissemination of all culture, but social change is the tool and prerequisite for educational thought. Education initiates social change and provides direction and purpose. Education prepares people for social change. Education determines the nature of social change that must be brought about. Education is the most powerful tool to bring about social revolution. Education can change society by providing opportunities and experiences that enable individuals to develop themselves to adapt to new needs and changing social philosophies. Healthy social progress requires careful planning in all aspects of social, cultural, economic and political life. Education must be planned in a way that meets the needs and aspirations of society as a whole.